Persistent streptococcal throat infection in a preparatory school for boys. - Briscoe, J. H. (Cambridge University Press, 1985)
An outbreak of streptococcal throat infection which took place in a preparatory school for boys (some of whom were choristers) over three terms from November 1983 to June 1984 is described. Typing of the organism revealed that four successive outbreaks, each due to a different type, had occurred. Thirty-nine per cent of the boys were affected, the incidence of infection being higher among boarders than day boys. Infection seemed to spread via the forms, dormitories and choir. Recurrent attacks occurred in 32% of infected boys. The complication rate was 8%. Treatment with penicillin was always effective but did not prevent reinfection. Suggestions for the management of an outbreak of sore throat in a school are given.